Paper based analytical platforms: A matrix adaptable approach to drug testing - Naga Prashant Koppuravuri; Suvarna Yenduri; Rukaiya Nabi; Pooja M; Aishwarya N; Sanika M; Sinchana Prakash (Talanta Open)
Paper-based analytical devices (PADs) are becoming increasingly popular for drug analysis in various matrices. These affordable, portable platforms come with a range of benefits, such as their user-friendly design, straightforward operation, and minimal need for sample preparation. This study evaluates the potential applications of PADs in drug testing with a particular emphasis on the adaptability of PADs in terms of their ability to handle various types of samples during the testing process. In this study, the design, manufacturing, and performance of PADs for drug detection, as well as the influence that different biological samples have on the performance of PAD performance were investigated. PADs are discussed in this paper, with respect to their applications in forensic sample analysis, point-of-care testing and illicit drug testing. The study demonstrates the flexibility of PADs as platforms for drug testing in varied matrices. The authors highlight the fact that PADs are inexpensive, portable, user-friendly, and need minimum sample preparation, which makes them effective instruments in a variety of situations, including research, law enforcement, and healthcare. On the whole, this paper highlights the versatility of PADs, emphasizing their role as adaptable platforms for drug testing within different matrices. Scientists and professionals can utilize these cutting-edge devices to improve the efficiency and accessibility of drug analysis.